Evaluation of knowledge base of hospital pharmacists and physicians on herbal medicines in Southwestern Nigeria - Titilayo O. Fakeye (Pharmacy Practice, 2008)
The use of herbal medicines among Nigerianpatients and the tendency to combine this class ofmedicines with allopathic drugs while on hospitaladmission have been on the increase. Earlierstudies show that community pharmacists fromNigeria believe that they need more training tocounsel patients on their use of herbal medications.Objective: To evaluate knowledge base, use,acceptability, attitudes and beliefs of hospitalpharmacists and physicians in South-westernNigeria on herbal products / phytopharmaceuticals/dietary supplements (HP/PP/DS).Methods: A 20-odd questionnaire including an 8-item herbal medicine question was used to assessthe knowledge of the physicians and pharmacists inthe area of pharmacology of HP/PP/DS. Effects ofdemographic information such as age, sex, yearpost graduation, years of experience and area ofspecialization on the scores obtained wereevaluated using Fisher´s exact tests. Level ofsignificance was set at p<0.05.Results: Pharmacists (51.4%) believed that thetraining they had was not adequate while physicians(44.6%) believed HP/PP/DS are not safe and 18.5%believed they are not effective. Pharmacovigilancecentres were not significantly used for adversereactions reported by patients. Pharmacists (67.6%)and physicians (29.3%) believedphytopharmaceuticals interact with other drugs.Year of graduation had a significant effect on theperception of the possibilities of interaction forpharmacists. 5.6% of the physicians and 62.4% ofthe pharmacists scored ≥50% with the questions onuse and interaction potentials of HP/PP/DS, withcadre and years of practice having significanteffects.Conclusions: There is a deficiency in the knowledgebase of physicians, especially on the pharmacologyand potential interaction of herbal medicines. Thereis an urgent need for the inclusion of pharmacologyof common herbal medicines in the curriculum ofNigerian medical degree and an improvement in thepharmacy curriculum in this area